2017
DOI: 10.1177/0022034517702331
|View full text |Cite|
|
Sign up to set email alerts
|

A Consensus-Based Set of Measures for Oral Health Care

Abstract: Increasingly more responsive and accountable health care systems are demanded, which is characterized by transparency and explicit demonstration of competence by health care providers and the systems in which they work. This study aimed to establish measures of oral health for transparent and explicit reporting of routine data to facilitate more patient-centered and prevention-oriented oral health care. To accomplish this, an intermediate objective was to develop a comprehensive list of topics that a range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 28 publications
0
35
0
Order By: Relevance
“…In general, most Patient‐Reported Outcomes Measures (PROMs) and Patient‐Reported Experience Measures (PREMs) that were found in this systematic review stem from Europe, whereas for the United States, there were more population‐level measures, measures assessing disease outcomes, and measures related to oral treatment and preventive services. Compared to Europe, the publications from the United States developed more measures for the use in electronic health records (EHRs) .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In general, most Patient‐Reported Outcomes Measures (PROMs) and Patient‐Reported Experience Measures (PREMs) that were found in this systematic review stem from Europe, whereas for the United States, there were more population‐level measures, measures assessing disease outcomes, and measures related to oral treatment and preventive services. Compared to Europe, the publications from the United States developed more measures for the use in electronic health records (EHRs) .…”
Section: Resultsmentioning
confidence: 97%
“…[1][2][3][4] Robust and comprehensive measures that collect routine data on the processes and outcomes of oral care health care may contribute to a more transparent, evidence-informed and person-centred care system. 5 These measures need to be transparent and should reflect health processes, outcomes, person/patient perception and costs that are associated with oral health care. 6,7 Measuring the quality of oral care using valid and reliable measures may enable various stakeholders, such as policymakers and dentists, to evaluate and improve the quality of care.…”
Section: Introductionmentioning
confidence: 99%
“…The acquisition of claims data as part of the overall ADVOCATE project has been described elsewhere [28,29]. An earlier study, using an extensive four-stage approach, which has been conducted as part of the ADVOCATE project, has defined measures that are considered relevant, important and useful for feedback information by oral healthcare stakeholders [30] (Supplementary Appendix 1). These measures will be used to compromise the patient self-reported online questionnaire.…”
Section: Feedback Informationmentioning
confidence: 99%
“…While the development process of most of these published measures has been comprehensive, only 4 studies reported on the additional scientific properties of the measures (e.g., validity, reliability) or tested the utility of measures in practice ( Herndon, Crall, et al 2015 ; Bhardwaj et al 2016 ; Hummel et al 2017 ; Neumann et al 2017 ). Robust measures that can be applied to routinely collected data would contribute to a more transparent, evidence-informed, and patient-centered oral health care system ( Baâdoudi et al 2017 ). The issue now may not be a lack of measures but rather the limited evidence that the measures developed so far have been explicitly demonstrated to be fit for purpose.…”
Section: Introductionmentioning
confidence: 99%